Economic control authorities: a reading of Algerian law (Milan Law Review, 2024)
The emergence of independent administrative authorities and their granting of repressive powers in matters of economic control are the result of the economic transformations that Algeria has experienced since the adoption of the free economic approach. Given the adoption of this approach, the judiciary was not prepared to examine the conflicts arising from this development, but remained unable to keep up with the pace and techniques. These new economic areas have led the legislator to grant repressive powers to independent supervisory authorities in most economic sectors. The repressive powers of independent police authorities result from the phenomenon of decriminalization, which involves the removal of the repressive power of the criminal judge in favor of other bodies and the replacement of criminal sanctions by administrative sanctions.
Keywords: judicial power; administrative sanctions; economic control authorities; banking commission